Long term comparison between reprocessed nuclear fuel cycles (Brazilian Journal of Radiation Sciences (BJRS), 2022)
Based on the idea of adopting closed fuel cycle in current pressurized water reactors (PWR) in order to reduce the use of natural uranium and recycle the spent fuel accumulated in the world inventory, this paper aims to compare two closed nuclear fuel cycles simulated at Model for Energy Supply Strategy Alternatives and their General Environmental Impacts (MESSAGE). The nuclear fuel cycles compared are: i) a closed fuel cycle with recovering of plutonium (Pu) to fabricate the mixed oxide (MOX) fuel; ii) a closed fuel cycle with recovering of a transuranic matrix to fabricate the transuranic fuel spiked with depleted uranium (TRU-U)O2. The comparison is based on the Brazilian nuclear energy system. They consider the time frame of 2019-2060 and the introduction of Angra 3 in the system. Advantages and disadvantages of using the strategy of operating with the different nuclear fuel cycles are shown, which include results regarding natural uranium consumption, spent fuel accumulation or utilization, nuclear waste and the nuclear fuel costs for both fuels.